Simulation the Behavior of Passive Rigid Pile in Sandy Soil - Mahdi O. Karkush; Ghofran S. Jaffar (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
This research studied the behavior of a rigid pile driven into sandy soil and subjected to soil movement. The behavior of the pile was simulated in two cases: loaded and unloaded. The modeled piles were made of aluminum and had a diameter (D) of 10 mm. Embankment loads were applied at three different distances from the face of the pile (2.5, 5, and 10) D. Strain gauges were fixed at four points along the pile shaft using a half-bridge configuration to measure the strains resulted from the lateral movement of the soil. The results obtained from the physical model were the lateral and vertical movements at the surface of the soil and the bending strain along the pile shaft. These results were analyzed numerically to calculate the bending moment, pile rotation, pile deflection, shear force, and soil reaction profiles. Some of these results were measured experimentally and others were calculated theoretically based on the measured strains. The maximum deflection of the axially loaded pile was more than that in the unloaded pile by 26%, 108%, and 159%, with the embankment at distances (2.5, 5, and 10) D, respectively. The rigid pile provided more resistance to the pressure generated from the soil movement.